2016
DOI: 10.21037/jtd.2016.10.74
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome after cardiac surgery

Abstract: Acute respiratory distress syndrome (ARDS) is a leading cause of postoperative respiratory failure, with a mortality rate approaching 40% in the general population and 80% in the subset of patients undergoing cardiac surgery. The increased risk of ARDS in these patients has traditionally been associated with the use of cardiopulmonary bypass (CPB), the need for blood product transfusions, large volume shifts, mechanical ventilation and direct surgical insult. Indeed, the impact of ARDS in the cardiac populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 84 publications
2
37
1
2
Order By: Relevance
“…The incidence of moderate-to-severe ARDS was 2.7%, which was also close to previous studies (that defined ARDS as a PaO 2/ FiO 2 ratio < 200) [1,2,26]. Nevertheless, provided high mortality of ARDS, it is still good to have a tool to warn the possibility of developing ARDS, especially in those with risk factors such as massive transfusion, previous cardiac surgery, long-time CPB [2,4], etc.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The incidence of moderate-to-severe ARDS was 2.7%, which was also close to previous studies (that defined ARDS as a PaO 2/ FiO 2 ratio < 200) [1,2,26]. Nevertheless, provided high mortality of ARDS, it is still good to have a tool to warn the possibility of developing ARDS, especially in those with risk factors such as massive transfusion, previous cardiac surgery, long-time CPB [2,4], etc.…”
Section: Discussionsupporting
confidence: 85%
“…It has been shown that PCT liberation predominantly depended on the use of CPB in cardiac surgery [18]. It is also known that the development of ARDS is associated with the use of CPB [4]. However, it is still unknown whether high PCT indicates a higher incidence of ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory response may be the cause of ARDS and blood transfusion during cardiac may cause transfusion-related acute lung injury (TRALI). [29] Both ARDS and TRALI are hazardous complications which complicate the postoperative period in COVID-19 patients.…”
Section: And Further Potential Effects Of Cardiac Surgerymentioning
confidence: 99%
“…Despite advances in CPB techniques and in preventive measures aimed at decreasing respiratory complications after cardiac surgery, postoperative acute respiratory distress syndrome (ARDS) occurs in 1−20% of patients, depending on inclusion criteria. [56][57][58][59] The use of V-A ECMO for refractory cardiovascular dysfunction after pediatric cardiac surgery has been described, but there is paucity of data on the use of postcardiotomy V-V ECMO. Respiratory distress and hypoxia are reported as indications for ECMO support in 2-30% of pediatric patients.…”
Section: Post-cardiotomy Veno-venous Ecmo For Respiratory Dysfunctionmentioning
confidence: 99%
“…57 ECMO use post Htx has been reported as high as 10%-15%. [58][59][60] The use of more marginal donor hearts may predispose to the need for PC-ECMO. Notably, Listijono and colleagues showed that its use apparently does not influence primary graft recovery or patient survival to discharge.…”
mentioning
confidence: 99%